2018
DOI: 10.1159/000489810
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Actions of Rotenone, an Inhibitor of Mitochondrial Respiratory Chain, on Ionic Currents and Miniature End-Plate Potential in Mouse Hippocampal (mHippoE-14) Neurons

Abstract: Background/Aims: Rotenone (Rot) is known to suppress the activity of complex I in the mitochondrial chain reaction; however, whether this compound has effects on ion currents in neurons remains largely unexplored. Methods: With the aid of patch-clamp technology and simulation modeling, the effects of Rot on membrane ion currents present in mHippoE-14 cells were investigated. Results: Addition of Rot produced an inhibitory action on the peak amplitude of INa with an IC50 value of 39.3 µM; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 37 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…The recording pipettes used had a resistance of 3–5 MΩ as they were immersed in different solutions described above. Patch-clamp recordings were made in whole-cell, cell-attached, or inside-out configuration by means of an RK-400 (Bio-Logic, Claix, France) or Axopatch 200B patch amplifier (Molecular Devices, Sunnyvale, CA, United States) (Huang et al, 2018; Lai et al, 2018). Liquid junctional potential was commonly nulled immediately before establishment of the seal.…”
Section: Methodsmentioning
confidence: 99%
“…The recording pipettes used had a resistance of 3–5 MΩ as they were immersed in different solutions described above. Patch-clamp recordings were made in whole-cell, cell-attached, or inside-out configuration by means of an RK-400 (Bio-Logic, Claix, France) or Axopatch 200B patch amplifier (Molecular Devices, Sunnyvale, CA, United States) (Huang et al, 2018; Lai et al, 2018). Liquid junctional potential was commonly nulled immediately before establishment of the seal.…”
Section: Methodsmentioning
confidence: 99%
“…Both animal and clinical studies [8,9,10,11,12,13] have revealed that continuous epileptic seizures can cause the dysfunction of mitochondria, which may act as a critical player in seizure-induced brain damage. It is well understood that prolonged seizures selectively affect Complex I enzyme activity in the mitochondrial respiratory chain, causing excessive oxidative and nitrosative stress, and resulting in neuronal cell injury or death in the hippocampus—which may induce succeeding epileptogenesis [5,12,14]. Consequently, the mitochondria may possess characteristics to determine the fate of neuronal survival after status epilepticus and play a role in therapeutic modification [5,12].…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms by which intranasal administration of rotenone induced persistent changes in intrinsic excitability of olfactory sensory neurons remain unclear. One possible mechanism is the acute action of rotenone that involves modulation of ion channels through the production of reactive oxygen species [22]. However, in this study, because rotenone administrated to the nasal cavity was washed out in dissection of olfactory epithelium before electrophysiological recordings, such long-lasting inhibition of ion channels by rotenone may be related with plasticity of neuronal excitability (Fig.…”
Section: Discussionmentioning
confidence: 86%